Multi‐Component Mesocrystalline Nanoparticles with Enhanced Photocatalytic Activity. Issue 51 (20th November 2020) - Ko, Min Jun; Park, Bum Chul; Koo, Thomas Myeongseok; Jeon, Yoo Sang; Kim, Myeong Soo; Kim, Young Keun
Abstract: Mesocrystals, consisting of small subunits, have gained research interests owing to their ability to simultaneously modify material‐specific properties and interactions among subunits. However, despite these unique characteristics, most mesocrystals are composed of a single material, and there is a disjunction between academic discovery and practical application. In this study, the synthesis of multi‐component mesocrystalline nanoparticles composed of Fe3 O4, ZnFe2 O4, and ZnO subunits using a polymerization induced heterogeneous nucleation method is reported. The structure has small ZnFe2 O4 and ZnO nanocrystals covering the Fe3 O4 crystallites. It exhibits not only magnetic and catalytic properties determined by the size of each subunit nanocrystal, but also enhances photocatalytic and colloidal properties that originates because of its crowded arrangement. The magnetically recoverable catalysts exhibit remarkable photodegradation of organic molecules under the irradiation of visible light for 1 h; thus, improving its applicability in purifying a large amount of wastewater during the daytime. Abstract : Magnetic–photocatalytic mesocrystalline nanoparticles via polymerization induced heterogeneous nucleation processes are desirable in environmental applications due to their rapid magnetic separation, visible light absorption, efficient photocatalytic activity, and dispersion stability in wastewater. This study suggests a new nanostructure not only exhibiting material‐dependent properties, but also utilizing synergetic properties of unit nanocrystals, simultaneously.